2021
DOI: 10.1038/s41467-020-20745-5
|View full text |Cite
|
Sign up to set email alerts
|

Preserving a robust CsPbI3 perovskite phase via pressure-directed octahedral tilt

Abstract: Functional CsPbI3 perovskite phases are not stable at ambient conditions and spontaneously convert to a non-perovskite δ phase, limiting their applications as solar cell materials. We demonstrate the preservation of a black CsPbI3 perovskite structure to room temperature by subjecting the δ phase to pressures of 0.1 – 0.6 GPa followed by heating and rapid cooling. Synchrotron X-ray diffraction and Raman spectroscopy indicate that this perovskite phase is consistent with orthorhombic γ-CsPbI3. Once formed, γ-Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 54 publications
(96 reference statements)
4
130
0
Order By: Relevance
“…Moreover, the thermodynamic barrier and activation energy are significantly influenced by strains, as compressive strain has been calculated to increase activation energy for black to yellow phase transition, thus improving perovskite phase stability. A study on CsPbI 3 powder also confirmed results observed on this films, showing that applying pressure in ambient conditions allows the gamma phase preservation even in moisture loaded air [46] . This improved stability was further explained by DFT calculations indicating a tilt in [PbI 6 ] 4− octahedra which favors the gamma phase instead of the delta phase [47] .…”
Section: Resultssupporting
confidence: 77%
“…Moreover, the thermodynamic barrier and activation energy are significantly influenced by strains, as compressive strain has been calculated to increase activation energy for black to yellow phase transition, thus improving perovskite phase stability. A study on CsPbI 3 powder also confirmed results observed on this films, showing that applying pressure in ambient conditions allows the gamma phase preservation even in moisture loaded air [46] . This improved stability was further explained by DFT calculations indicating a tilt in [PbI 6 ] 4− octahedra which favors the gamma phase instead of the delta phase [47] .…”
Section: Resultssupporting
confidence: 77%
“…In the plethora of possible halide perovskite compositions, cesium lead iodide perovskite (CsPbI 3 ) remains a key material for single-junction solar cells, since its red-emitting black phase has an optimal bandgap (1.6-1.8 eV) 1 for matching the solar spectrum. Furthermore, being all-inorganic, it has a great potential for developing highly stable perovskite solar cells (PSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the black phase of CsPbI 3 is only stable at high temperatures and it otherwise quickly converts to a nonemissive yellow phase with a bandgap (E g ) not suitable for photovoltaic applications. 1 Using high-resolution in situ synchrotron X-ray diffraction (XRD) measurements, Marronnier et al demonstrated that CsPbI 3 adopts a α-cubic (black) phase only above 645 K, which upon cooling transforms into a β-tetragonal (black) phase (510 K) and then to a metastable γ-orthorhombic (black) phase (325 K). Finally, the γ-orthorhombic (black) phase converts into a δ-orthorhombic (yellow) phase at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Application of high pressure followed by heating and rapid quenching allows to obtain a material that shows good stability in air. [91] However, also full reversibility of pressure-induced change might be interesting for materials and applications that require transient changes in the electronic properties.…”
Section: Ge-based Compoundsmentioning
confidence: 99%
“…[118] A different route to the stabilization of the desired phase might be high pressure, as proposed by recent works. [91] The authors applied a pressure between 0.1 and 0.6 GPa to δ-phase-CsPbI 3 followed by heating and rapid quenching. The resulting γ À CsPbI 3 can be retained after releasing pressure to ambient conditions and, in contrast with the previous methods, it shows a good stability to air moisture for up to 10 days.…”
Section: Other Structuresmentioning
confidence: 99%